PENGARUH PARAMETER PERMESINAN TERHADAP BURR FORMATION PADA PROSES MILLING DENGAN CNC ROUTER ALUMINIUM SHEET 1100 - fariq urbeyni (Jurusan Teknik Mesin Fakultas Teknik Universitas Bangka Belitung, 2020)
This study aims to determine the burr formation value of aluminium sheet 1100 object using the milling router machining method with depth parameters feeding (1mm ; 1,5mm ; 2mm), feeding (100 mm/minute ; 200 mm/minute ; 300 mm/minute), speed (5000rpm ; 8000rpm ; 12000rpm) and coolant (coolant ; air ; oil SAE 40). This resarh was carried out in a robotics laboratory majoring in electronics engineering at the bengkalis state polytechnic campus.The samples used were 100x60 mm in size with 27 pieces which would be treated differently by varying the end mill tool diameter, feeding depth, feeding, speed, and coolant. The measurment used to measure the burr formation of the workpiece is a microscope USB, data analysis techniques used are the taguchi and ANOVA methods. The results showed that the lowest burr value was obtained at 1mm depht, 6mm tool, 50 m/minute feeding, oil cooler and 5000 rpm speed ie 0,2288 while the hihest was obtained at 1,5mm depht, 5mm tool, 50 m/minute feeding, coolant cooler and 12000 rpm speed ie 0,590967. Based on the analisys of varian (ANOVA) that the significant parameter in influencing the burr formation is the tool and coolant